2020
DOI: 10.47125/jesam/2020_2/04
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Link between Environmental Practices and Financial Performance: an Empirical Study

Abstract: Ongoing environmental deterioration has led governments and other institutions to pay closer attention to pollution problems as pollutant emissions can significantly influence and constrain economic growth. Most countries on the American continent use the ISO 14001 standard and the number of new certifications grows year by year. This work empirically explores the influence of environmental management system based on ISO 14001 certifications upon the financial performance of Colombian companies, 133… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that firm size [16,25] and government subsidy [58] significantly moderate the relationship between green innovation and firms' financial performance. In addition, previous studies have also found that ISO14001 [1,24] is a critical variable in predicting firms' environmental performance. In addition, control variables mentioned in previous studies included the firm fixed asset ratio [3], research and development investment [20,59], and gearing ratio [1,59].…”
Section: Control Variablesmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have shown that firm size [16,25] and government subsidy [58] significantly moderate the relationship between green innovation and firms' financial performance. In addition, previous studies have also found that ISO14001 [1,24] is a critical variable in predicting firms' environmental performance. In addition, control variables mentioned in previous studies included the firm fixed asset ratio [3], research and development investment [20,59], and gearing ratio [1,59].…”
Section: Control Variablesmentioning
confidence: 93%
“…First, a large portion of the studies is based either on cross-sectional data obtained from questionnaires [15][16][17][18][19] or using panel data but only based on the consideration of the composite construction of "green innovation" [20][21][22], resulting in inconsistent findings between green innovation and corporate financial performance [14,23]. Second, most studies focus only on the single impact of green innovation on firms' financial performance [1,24,25] or on firms' comprehensive performance indicators [26,27], and the literature lacks comparative studies on the performance consequences of different dimensions of green innovation (e.g., financial performance and environmental performance) [23]. Green innovation is a complex of corporate efficiency and legitimacy.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature in the field has explored how investors are looking for firms capable of developing mitigation, adaptation, and climate risk strategies (Bender et al, 2019;Ren et al, 2022;Wu et al, 2022). In addition, the number of studies into the relationship between environmental and financial performance is growing (Barcellos de Paula et al, 2020;Kumar & Dua, 2021;Tao et al, 2022;Zhang, Wang et al, 2022). Nonetheless, to the best of our knowledge, no elements in the current literature have determined whether there is a relationship between environmental and financial performance, measured by Return on Assets (ROA), in Latin American firms.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they are more heedful of financial returns and their contribution to the society and environment (Akbar et al 2021). Considering the stakeholders' requirements and institutional environmental pressures, the link between environmental sustainability and corporate financial performance is catching the spotlight (Rabadán et al 2019;Jan et al 2019;de Padua et al 2020). It is believed that this link is essential to the commercial success (Chen and Liu 2018).…”
Section: Introductionmentioning
confidence: 99%